Flashcard Learning of Science Content on Plant Parts and Their Functions to Improve Elementary School Student Learning Outcomes - Ni Wayan Rani Sumarsani; Ni Wayan Rati; Adrianus I Wayan Ilia Yuda Sukmana (Undiksha Press, 2025)
Learner-centered learning can facilitate understanding, foster creativity, and connect the material to real life. However, the implementation of IPAS is still monotonous with minimal interactive media, so students tend to be passive, lack understanding of concepts, and have low learning outcomes. This research involved 30 students as research subjects. This study aims to develop flashcard-based learning media to improve the learning outcomes of fourth-grade elementary school students in the subject of plant parts and their functions. The development uses the ADDIE model, which includes analysis, design, development, implementation, and evaluation. The method used in this experiment was a questionnaire, with analysis using qualitative descriptive analysis (expert input) and quantitative analysis (numerical data). The flashcards were created using Canva, featuring images, text, and barcodes linking to videos and interactive quizzes. Expert validation indicated a validity index of 3.65 (acceptable for use). The practicality test received positive responses from teachers (100%) and students (94%). The effectiveness test using pretest-posttest showed a significant improvement (p < 0.001). Therefore, Canva-based flashcards are recommended as an innovative alternative in learning, particularly for plant-related topics and their functions. This study has implications as a model or example in designing interactive flashcard-based learning media created through the Canva platform, which can serve as an innovative solution to address monotonous and less interactive IPAS learning in elementary schools.